ASAM HIDROKSIINDOLASETIK 5 (5-HIAA) AIR KEMIH DI KANKER KOLOREKTAL - Mansyur Arif; Yosep F. Tallulembang; Burhanuddin Bahar; Ibrahim Abd. Samad; Ibrahim Labeda (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Colorectal cancer, in fact is one of the three most malignant tumour types found in the world. Early detection is recommended to find out the problem and will affect better life expectancy. Various study have been conducted looking for a test that can be easily, non invasive, inexpensive, no special equipment and skills required such as by detecting 5-hidroxyindolacetic acid that can be found in the urine. The aim of this study was to analyze 5-HIAA in the urine of colorectal cancer patients. The study was conducted at the Clinic and Surgical Ward, and Clinical Pathology Laboratory, at Dr. Wahidin Sudirohusodo Hospital in Makassar during the period May–August 2011. The study was conducted on 42 patients and 45 controls ranging from 35−74 years old and 20−52 years old, respectively. The diagnosis is based on the histopathological and most were in stage III of adenocarcinoma profile. Rated of 5-HIAA colorectal cancer the highest is in the value of 4–6 and all normal control had value of 1–3. There is a significant association between 5-HIAA and colorectal cancer, that shown the highest stadium of colorectal cancer, and the highest value of urine 5-HIAA. The ideal cut-off point for screening is two (2) with its sensitivity and specificity values are 100% and 88. 9%, respectively. 5-HIAA urine test can be used as a tumor marker for colorectal cancer in conjunction with other supporting tests. Further study is needed to determine the cut-off point with a various clinical stage.